2020
DOI: 10.1142/s0192415x20500147
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Medicinal Plants in Cardiovascular Disorders: Benefits and Risks

Abstract: Many cultivated and wild plants are used for the management of various diseases, specifically renal and hepatic diseases and those of the immune and cardiovascular systems. In China, medicinal plants from ancient to modern history have been used in patients with angina pectoris, congestive heart failure (CHF), systolic hypertension, arrhythmia, and venous insufficiency for centuries. The latest increase in the fame of natural products and alternative medicine has revived interest in conventional remedies that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 125 publications
0
7
0
2
Order By: Relevance
“…Advances in clinical research and quality control have shown a greater value of herbal medicine in the treatment and overcoming of many diseases. Recent works report promising potential regarding the use of plants in the treatment and/or prevention of several hard-to-cure diseases, such as atherosclerosis [ 5 , 6 ], cancer [ 1 , 2 , 3 , 7 , 8 ], cardiovascular diseases [ 9 , 10 , 11 , 12 ], diabetes [ 8 , 13 , 14 ], and neurological disorders [ 4 , 15 , 16 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in clinical research and quality control have shown a greater value of herbal medicine in the treatment and overcoming of many diseases. Recent works report promising potential regarding the use of plants in the treatment and/or prevention of several hard-to-cure diseases, such as atherosclerosis [ 5 , 6 ], cancer [ 1 , 2 , 3 , 7 , 8 ], cardiovascular diseases [ 9 , 10 , 11 , 12 ], diabetes [ 8 , 13 , 14 ], and neurological disorders [ 4 , 15 , 16 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a wide pharmaceutical armamentarium, cardiovascular diseases are among the most frequent causes of death in the world and great efforts are spent to develop new chemical entities or explore the efficacy of natural compounds and their mechanisms of action (61). In this context, B. serrata has shown positive effects on the cardiovascular system.…”
Section: Boswellia In Cardiovascular Diseasesmentioning
confidence: 99%
“…In some cases, co-administration of herbs with conventional drugs could result in adverse effects that are distinct from the pharmacological effects of either the drug or the herb. For example, garlic and Ginko react with aspirin with the potential side effects of increasing the risk of bleeding whereas hawthorn interacts with digoxin to cause arrhythmias (Naveed et al 2020).…”
Section: Issues Relating To Interactions Of Herbs With Metabolizing Enzymes and Allopathic Drugsmentioning
confidence: 99%